If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -6x = 102x Solving 18 + -6x = 102x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-102x' to each side of the equation. 18 + -6x + -102x = 102x + -102x Combine like terms: -6x + -102x = -108x 18 + -108x = 102x + -102x Combine like terms: 102x + -102x = 0 18 + -108x = 0 Add '-18' to each side of the equation. 18 + -18 + -108x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + -108x = 0 + -18 -108x = 0 + -18 Combine like terms: 0 + -18 = -18 -108x = -18 Divide each side by '-108'. x = 0.1666666667 Simplifying x = 0.1666666667
| 4-6C=-5 | | 3x-7=-8 | | 8(x-2)=-4(x+1)+22 | | 13-3p=-5(3+2p) | | 6(x+3)=14x-26 | | -1.6x=30.4 | | -2x+5=39 | | 98X+56=4X+7 | | -3(x+n)=x | | xf-xg=h | | .3-.67(2)=n | | 3x+12y=57 | | 9x-2y=19 | | 26x+21=-39x-6 | | 4.8(x-2)=-0.2x+30.4 | | 9x-4=2x+24 | | 9x=2x+42 | | 8(7-y)=-24 | | 18x+15=9x+34 | | 5x-2=43 | | 9x+4=40 | | 7x+5=7x+5 | | 11x-4=6x+6 | | 2(6k-1)=-38 | | 4(x-4)+64=-2x | | 6(x-2)=-2x+28 | | .3-.67(-2)=x | | 4.7(x-1)=-0.3x+20.3 | | 3x+12=3x+22 | | 8x-5=4x+3 | | 5(x-3)=-3x+25 | | 3(2x+5)=39 |